The Comparison of the Discovery Learning and Project Based Learning and their Influences to Student’s Motivation to Learn Conditional Structure Programming - Mustikaningrum, Dian; Maryono, Dwi; Yuana, Rosihan Ari (Universitas Sebelas Maret, 2017)
The research aims to know (1) the differences of the influence of discovery learning and project based learning combined with college ball model’s influence to student’s achievement in conditional structure programming; (2) the differences of learning interest influences to students’ learning achievement; and (3) the effect of interaction between learning-model implementation and students’ interest to students’ learning achievement. The population of this research was students of class X MM in SMK N 6 Surakarta. The sample of this research contained the whole population include X MM 1 and X MM 2 class. This research used quasi experimental method postest only control group design. Data were collected by questionairre, for students learning interest data, and test for the data of students’ learning achievement. Those data were analyzed with two-way Anova test with different content of cell, followed with double comparison of Scheffe’s method with level of significance 0,05. The results showed that (1) there were no significance differences between discovery learning model and project based learning combined with college ball to students’ learning achievement in conditional structure programming. The students taught with project based learning combined with college ball had no better significance learning achievement than those who were taught with discovery learning, although the score of the students who were taught with project based learning combined with college ball had better than those who were taught with discovery learning; (2) there were significance difference between learning interest to students’ learning achievement. Students with high interest had better learning achievement than the students with low interest, but students with high interest had the same learning achievement as those with middle interest and students with middle interest and low interest did. ; (3) there was no effect interaction between learning-model implementation and students’ learning interest to their learning achievement..This work is licensed under a Creative Commons Attribution-ShareAlike 4.0 International License.